Mediating American hospitality: Mark Zuckerberg's challenge to Donald Trump?. (December 2021) - Winch, Alison; Little, Ben
In 2017, Facebook founder and CEO, Mark Zuckerberg, travelled America with a former White House photographer who took pictures of him sharing meals with families, workforces and refugee communities. These were then posted to Zuckerberg's Facebook page, usually with a post by Zuckerberg drawing attention to socioeconomic issues affecting different American communities. This article argues that Zuckerberg is mediated on this tour as a worthy populist contender to Donald Trump, albeit of a centrist, liberal, corporate kind. In particular, divisions along the lines of race, migration and class, which have been appropriated and emphasised by Trump, are apparently bridged and resolved through the representation of Zuckerberg, and the promotion of Facebook as a mediated fulcrum for civil society. Zuckerberg is pictured sharing food with, for example, Republican voters in Ohio and Somali migrants in Minnesota. We investigate how the differences projected between Zuckerberg and Trump pivot on the commodification of hospitality, particularly the mediation of shared meals, American hospitality, masculinity and 'diversity work'. We contextualise this analysis within an understanding of how Silicon Valley's monopoly capitalism perpetuates inequalities in its workforces and through its product design. We also attempt to make sense of the different social actors involved in Zuckerberg's mediated 'Year of Travel', including the PR team, the people in the photographs, the commenters, as well as the users of Facebook. Through these contextualisations, we argue that this mediated contestation of hospitality – who is welcome in American society, who is not and why – is central to understanding the tensions in contemporary American political culture.